Residential building rehabilitation in Porto historic center: Case study analysis by using a simulation model. (June 2022) - dos Reis, Alexandre Soares; Vaquero, Petra; Dias, Marta Ferreira; Tavares, Alice; Costa, Aníbal; Fonseca, Jorge
Abstract: Nowadays, rehabilitation in historic centers can become a challenge due to the restrictions concerning the requirements for the building envelope. Portugal has conducted studies to define the maximum U values [W/(m 2 K)] for single building components based on the indoor temperature. Despite the relative humidity being crucial for thermal comfort, the current Portuguese scheme for energy certification of buildings does not consider it. Additionally, it is essential to know that most of the dwellings in Portugal are in a fleet-float regime due to cultural habits and energy poverty. Therefore, increasing the insulation thickness of exterior walls might not have a relevant impact on the indoor temperature. There is even the risk of harming the authenticity of the built heritage. Using a calibrated dynamic simulation model developed with TRNSYS software, we found that, in winter, the effect of external wall insulation on the indoor temperature is tiny. Results suggest that maximum U values [W/(m 2 K)] for exterior walls might be over-defined. Further studies of cost-optimal levels should be conducted with calibrated models in a free-float regime to define the maximum U values [W/(m 2 K)] of external walls for this type of buildings.